Prinsip Akuntansi Syariah dalam Kerangka Sistem Ekonomi Syariah (Kajian QS. Al-Baqarah: 282) - Ziyad, Najib Prassojo; Athoillah, Muhammad; Bisri, Hasan (Sharia Journal and Education Center Publishing, 2026)
This study examines the concept of sharia accounting within the framework of the sharia economic system based on the normative foundation of Qur’an Surah Al-Baqarah verse 282. The main issue addressed in this research is how the values embedded in the verse can be understood as fundamental principles of sharia accounting and their relevance to contemporary sharia economic practices. The purpose of this study is to identify and analyze the principles of accountability, transparency, justice, and responsibility derived from QS. Al-Baqarah verse 282 and to relate them to modern sharia accounting concepts. This research employs a qualitative approach using a thematic interpretation (maudhu‘i) method by analyzing linguistic aspects, the circumstances of revelation (asbāb al-nuzūl), as well as classical and contemporary Qur’anic interpretations, which are then contextualized within the framework of sharia accounting. The findings indicate that the command to record transactions (faktubūh) reflects the principles of accountability and transparency in safeguarding the clarity of rights and obligations among parties. The value of justice (‘adl) emphasizes the importance of ethical conduct and integrity in financial recording, while the role of scribes and witnesses represents a form of social control comparable to auditing mechanisms. In conclusion, QS. Al-Baqarah verse 282 serves as a philosophical and theological foundation for the development of a sharia accounting system that integrates spiritual, social, and professional values in line with the objectives of sharia (maqāṣid al-sharī‘ah).